Peningkatan Kemampuan Operasi Hitung Pecahan Menggunakan Model Pembelajaran Kontekstual Pada Siswa Kelas VII di MTsN 8 Kebumen - Tursini Tursini (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2022)
This study aims to improve student learning achievement in Basic Competency: (1) explain and add and subtract two fractions with different denominators; and (2) solving problems related to addition and subtraction of two fractions with different denominators. The dependent variable (Y) in this class action research is the ability to operate arithmetic fractions. While the independent variable (X) is a contextual learning model. The form of this research is classroom action research with a cycle model, each cycle consisting of four stages, namely, planning, implementing action, observation and reflection, as a population (subjects given action) class VII D students of MTs N 8 Kebumen. Based on the results of the existing data analysis meeting, it can be seen that there has been an increase in results. In the initial conditions of student learning completeness 44%. With the use of the Contextual Learning Model, student mastery in cycle I became 72%. In cycle II, student learning mastery increased to 85%. From the entire cycle carried out, it can be concluded that the Contextual Learning Model can improve the ability to calculate fraction operations